2008
DOI: 10.1140/epja/i2008-10616-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of heavy baryon spectroscopy

Abstract: The recent observation at CDF and D0 of Σ b , Σ * b and Ξ b baryons opens the door to the advent of new states in the bottom baryon sector. The states measured provide sufficient constraints to fix the parameters of phenomenological models. One may therefore consistently predict the full bottom baryon spectra. For this purpose we have solved exactly the three-quark problem by means of the Faddeev method in momentum space. We consider our guidance may help experimentalists in the search for new bottom baryons a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
171
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(190 citation statements)
references
References 39 publications
15
171
3
1
Order By: Relevance
“…Besides, a number of new Ξ c and Ξ ′ c states have been also discovered recently [2]. As can be seen all known experimental states fit nicely into the description of our model not leaving too many possibilities open for the assigned quantum numbers as we resume in Table 3.…”
Section: Statesupporting
confidence: 69%
See 1 more Smart Citation
“…Besides, a number of new Ξ c and Ξ ′ c states have been also discovered recently [2]. As can be seen all known experimental states fit nicely into the description of our model not leaving too many possibilities open for the assigned quantum numbers as we resume in Table 3.…”
Section: Statesupporting
confidence: 69%
“…The mass difference between states belonging to the3 F and 6 F representations do also contain the dynamics of the light diquark subsystem, hard to accommodate in any heavy quark mass expansion. Therefore, exact solutions of the three-body problem for [2]. The results are shown in Table 1 compared to experiment and other theoretical approaches.…”
Section: Heavy Baryonsmentioning
confidence: 99%
“…Predictions of ∼ 3000 ± 40 MeV for the negative-parity Ω c states, and an analogous range for the Ω b states, have been made by several authors [10,[15][16][17][18][19][20][21][22][23][24][25][26][27]. (The last paper treats only 2S levels, identifying the states at 3066, 3119 MeV as candidates for J P = 1/2 + , 3/2 + , respectively.…”
Section: Alternative Interpretationsmentioning
confidence: 89%
“…Finally, to make contact with our previous studies of the heavy baryon spectra [8,9], the linear potential is screened at long distances,…”
Section: −2mentioning
confidence: 99%
“…The best testing ground for this purpose are baryons made of three distinguishable quarks, with one of them light. As compared to singly heavy baryons, they are free of the uncertainties of the interaction between light quarks [8], whose spin-dependent part would be dominant, and the light quark kinematics [9]. Unlike triply heavy baryons, there exist pairs of quarks with total spin 0 in a relative S wave, whose contribution will become crucial to study the spin splittings recently reported by nonperturbative lattice QCD [10][11][12].…”
Section: Introductionmentioning
confidence: 99%